2020
DOI: 10.1007/s10705-020-10088-4
|View full text |Cite
|
Sign up to set email alerts
|

Upland rice yield enhanced by early nitrogen fertilization on previous palisade grass

Abstract: High grain yields of upland rice (Oryza sativa L.) can be achieved in no-tillage systems. However, managing nitrogen (N) fertilization for rice in succession to forage grasses is a challenge because forage residues change N cycling and increase microbial immobilization of N, thereby reducing N availability to the subsequent cash crop. In the present study, two field experiments were conducted to determine if applying all or part of the N fertilizer on preceding palisade grass (Urochloa brizantha) and ruzigrass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 42 publications
(70 reference statements)
1
13
0
Order By: Relevance
“…Probably, ruzigrass had low N utilization efficiency and its released N was a source for microbial activity, making it unavailable to subsequent common bean (Parton et al., 1988; Rosolem et al, 2004, Rosolem et al., 2017). These findings are in agreement with previous studies (Momesso et al., 2020; Rocha et al., 2019). Lastly, the success of early N fertilization on cover crops is dependent on weather conditions in each experiment‐year (Figure 1).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Probably, ruzigrass had low N utilization efficiency and its released N was a source for microbial activity, making it unavailable to subsequent common bean (Parton et al., 1988; Rosolem et al, 2004, Rosolem et al., 2017). These findings are in agreement with previous studies (Momesso et al., 2020; Rocha et al., 2019). Lastly, the success of early N fertilization on cover crops is dependent on weather conditions in each experiment‐year (Figure 1).…”
Section: Discussionsupporting
confidence: 94%
“…However, this application has high risk of N losses because the N is susceptible to NO 3 leaching by rainfall, especially in tropical region that has intense rainy periods (Rosolem et al, 2017;Zhao et al, 2016). From the scientific literature standpoint, studies in the same region with early N applications on cover crops reported similar results in upland rice (Oryza sativa L.) yield (Momesso et al, 2020) and contrary results in maize and soybean [Glycine max (L.) Merr.] yields (Momesso et al, 2019;Tanaka et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The resulting increases in soil microbial activity further promote crop residue decomposition to release nutrients and enhance crop yields [17][18][19]. However, crop residues only partially replenish soil nutrients, and the application of N fertilizer in grass crop rotation systems is still necessary to maintain cash crop development and yields [20,21]. N fertilization promotes increased soil organic matter (SOM) and potentiates the effects of liming on plant development, microbial activity, crop residue decomposition, and nutrient cycling.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the lower DM production of ruzigrass, the species has been used preferentially over other grasses, such as Urochloa brizantha, for the production of forage in ICLS because of its ease of management in desiccation, high yield, palatability, quality nutritional value for animal feed, and adaptability to climate conditions during the off-season (Castro et al, 2015;Nascente et al, 2013). Lower DM production by ruzigrass than by palisade grass has been reported previously (Momesso et al, 2019;Momesso et al, 2020) and may reflect the tolerance of guineagrass and palisade grass to poor soils. Studies have shown that palisade grass has a higher tolerance to acid soil and high soil levels of aluminum, higher biomass yield (Fortes et al, 2008;Timossi et al, 2007), and a higher capacity of regrowth and straw persistence than ruzigrass (Felismino et al, 2012).…”
Section: Forage Productionmentioning
confidence: 98%